Acinar cell carcinoma of exocrine pancreas in two horses - de Brot, Simone; Junge, Hannah; Hilbe, Monika (Elsevier, 2014)
Two horses were presented with non-specific clinical signs of several weeks' duration and were humanely destroyed due to a poor prognosis. At necropsy examination, both horses had multiple small, white nodules replacing pancreatic tissue and involving the serosal surface of the abdominal cavity, the liver and the lung. Microscopically, neoplastic cells were organized in acini and contained abundant (case 1) or sparse (horse 2) intracytoplasmic zymogen granules. Immunohistochemically, both tumours expressed amylase and pan-cytokeratin, but not insulin or neuron-specific enolase. In case 2, a low percentage of neoplastic cells expressed glucagon and synaptophysin. The presence of zymogen granules was confirmed in both cases by electron microscopy and occasional fibrillary or glucagon granules were observed in cases 1 and 2, respectively. A diagnosis of pancreatic acinar cell carcinoma was established in both horses.